Systematic review and meta-analysis of biomarker proinflammation of depression in traumatic brain injury - Ate, Andisty; Wariki, Windy; Warouw, Finny; Pertiwi, Junita Maja (International Journal of Research in Medical Sciences, 2022)
Depression is one of the long-term complications of traumatic brain injury (TBI) associated with the inflammatory process. This study aims to analyze the role of proinflammatory biomarkers on depression due to TBI and determine the types of proinflammatory biomarkers of depression in TBI. This systematic review and meta-analysis used the preferred reporting items for systematic reviews and meta-analyses (PRISMA) protocol with the population, intervention, comparison, outcome method. The selected research articles consisted of 4 cohort studies and 2 cross-sectional studies. Participants were all participants who experienced TBI without any previous infectious disease and neurobehavior disorders. Article searches are limited to the last 10 years using digital libraries including Pubmed, Science Direct, Wiley, Google Scholar. Assessment of the risk of bias using the ROBINS-1 tool, research quality using the GradePro application, and meta-analysis using review manager software 5.4.1. The results of a meta-analysis of proinflammatory biomarkers of depression using 2 cross-sectional studies showed a risk of bias and a moderate level of certainty. The most common types of proinflammatory biomarkers are IL-6, TNF-α, and IL-10. These proinflammatory biomarkers are markers of depression in TBI and have an effect on depression in TBI, especially in recurrent TBI and high post-traumatic stress disorder with depression accompanied by an increase in the concentration value of these biomarkers. Increased proinflammatory biomarkers IL-6, TNF-α, and IL-10 were found in depression with TBI. This proinflammatory biomarker has a significant relationship so that it can be used as a marker of depression in TBI.